PERT PROPOSAL IN PROGRAM EVALUATION THROUGH GRAPH MATHEMATIC TECHNIQUE - Sánchez Algarra, Pedro; Anguera Argilaga, María Teresa (Anales de Psicología / Annals of Psychology)
Graph analysis was always of the mathematical-geometric nature. It has not been used on Behavioral Sciences, with few wxcwptions, and it can become of useful instrument in several fields. In this article it is proposed as application to PERT (Project Evaluation and Review Technique). The PERT graphics are the main axes of planning in program evaluation; also, they are relevant to take decisions during the process of program implementation and program evaluation. Its characteristic rigor constitues a basic guarantee for efficacy and effectiveness of program.